24th COLLEGIUM RAMAZZINI STATEMENT - PREVENTION OF WORK-RELATED INFECTION IN THE COVID-19 PANDEMIC - Ramazzini, Collegium (European Journal of Oncology and Environmental Health, 2020)
The Collegium Ramazzini is an independent, international society comprised of 180 physicians and scientists from 35 countries. Its mission is to increase scientific knowledge of the environmental and occupational causes of disease and to transmit this knowledge to decision-makers, the media and the global public to prevent disease, promote health and save lives. The Collegium Ramazzini calls urgently for preventive measures internationally and in every country to reduce risk of COVID-19 infection in workers.The COVID-19 pandemic has affected every country in the world, caused confirmed illness in more than 3 million people, unconfirmed disease in millions more, and more than 200,000 deaths. At present, there is no vaccine and no medical treatment for COVID-19. Pandemic control must therefore rely entirely on measures that reduce the spread of infection, flatten the epidemic curve, and gain time to develop more effective responses.Workers whose occupations put them in contact with infected persons and the public are at greatly increased risk of disease and death and have suffered disproportionately in the COVID-19 pandemic. Workplaces have repeatedly been the source of serious outbreaks. Protection of all workers, and especially workers who continue to provide essential services during the pandemic as well as vulnerable workers, must be a top priority at every stage. SARS-CoV-2 enters the body though inhalation. Lungs and airways that have been damaged by personal exposures such as smoking or vaping, by toxic environmental exposures such as PM2.5 air pollution or by occupational exposures such as silica dust, asbestos, coal dust, fumes and gases are at heighted risk of infection, severe outcomes and death. High-Risk Workers. Workers whose occupations put them in contact with infected persons and the public are at greatly increased risk of COVID-19 infection. These workers require heightened protection. A partial listing of high-risk workers is the following: - Very High Risk: Health care workers, paramedics, police, firefighters, airline personnel, transport workers, drivers, sales and service personnel, cleaners, mortuary workers, migrant workers, volunteers, and religious professionals. - High Risk: Security service workers; hotel and food service workers; cruise industry workers; and military personnel pressed into pandemic service; workers in infrastructure, manufacturing, meatpacking, construction, mining and other occupations with crammed workplaces and poor provision of occupational and personal hygiene measures. - Workers at Increased Vulnerability: Older workers, workers with underlying medical conditions, such as hypertension, obesity, heart disease and cancer; workers occupationally exposed to dusts, gases and fumes; workers of low socio-economic status; workers exposed to high levels of ambient air pollution; and workers in developing countries. The Collegium Ramazzini calls on governments at all levels – national, state or provincial, and local - and on all employers - large and small, public and private - to fulfill their responsibilities to protect the health of all workers in the COVID-19 pandemic.